Statistical Inference for the Parameter of Rayleigh Distribution Based on Progressively Type-I Interval Censored Sample (Communications in Mathematical Research, 2021)
In this paper, the estimation of parameters based on a progressivelytype-I interval censored sample from a Rayleigh distribution is studied. Differentmethods of estimation are discussed. They include mid-point approximation estimator, the maximum likelihood estimator, moment estimator, Bayes estimator, samplingadjustment moment estimator, sampling adjustment maximum likelihood estimatorand estimator based on percentile. The estimation procedures are discussed in detailsand compared via Monte Carlo simulations in terms of their biases.